The Induction of Endothelial Autophagy and Its Role in the Development of Atherosclerosis - Hua, Yunqing; Zhang, Jing; Liu, Qianqian; Su, Jing; Zhao, Yun; Zheng, Guobin; Yang, Zhihui; Zhuo, Danping; Ma, Chuanrui; Fan, Guanwei (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Increasing attention is now being paid to the important role played by autophagic flux in maintaining normal blood vessel walls. Endothelial cell dysfunction initiates the development of atherosclerosis. In the endothelium, a variety of critical triggers ranging from shear stress to circulating blood lipids promote autophagy. Furthermore, emerging evidence links autophagy to a range of important physiological functions such as redox homeostasis, lipid metabolism, and the secretion of vasomodulatory substances that determine the life and death of endothelial cells. Thus, the promotion of autophagy in endothelial cells may have the potential for treating atherosclerosis. This paper reviews the role of endothelial cells in the pathogenesis of atherosclerosis and explores the molecular mechanisms involved in atherosclerosis development.